The shepherd imagery in Zechariah 9-14 - O'Kennedy, Daniël Francois (Old Testament essays, 2009)
The shepherd image emphasises the shepherd's role as leader, provider and protector. In Zechariah 1-8 one finds references to specific leaders, for example king Darius, the high priest Joshua and the governor Zerubbabel. Zechariah 9-14 has no reference to a specific leader. On the contrary, one finds 14 occurrences of the shepherd image as a reference to God or earthly leaders (civil and religious). The question posed by this article is: Which different perspectives are portrayed by this image? The use of the shepherd image in Zechariah 9-14 cannot be restricted to one perspective or meaning like in some Biblical passages (cf. Ps 23). The following perspectives are discussed: God as the good shepherd (Zech 9:16; 10:3b, 8); the prophet as shepherd (11:4-14); the three bad shepherds (11:8); the worthless shepherd, who deserts his flock (11:15-17); God's shepherd, his associate (13:7-9) and even a viewpoint that God is indirectly portrayed as an "uncaring shepherd" (cf. 11:4-17) .